The Spectrum of Seizure Disorders in Children at a Secondary Care Hospital in Saudi Arabia - Bin Alamir, Abdulrahman; Jalis, Mufid S. (International Journal of Child Health and Nutrition, 2023)
Objective: This study was conducted to find out the presentation, clinical features, diagnosis, and outcome of seizures in children in a secondary care hospital. Methodology: This was a prospective, cross-sectional analytical study conducted from September 2018 to April 2020 in a secondary care hospital in the Kingdom of Saudi Arabia. Children presented with seizures to the hospital were included and studied for the demographic profile, clinical presentation, diagnosis, and course of the disease. Results: A total of 73 cases were included in the study. Out of these, 48 (65.8%) were in the age group of 1-5 years, while 25 (34.2%) were in the age group of 6-14 years. Males were 33 (45.21), while females were 40 (54.8%). More than half of the cases were already diagnosed 43 (58.9). Generalized tonic-clonic seizures were the most common seizure type in the patients. The most common etiology of seizures was febrile seizure, followed by epilepsy. Conclusion: Seizures in children are not uncommon presentations with varying profiles in various regions of the world. Febrile seizures and epilepsy are the commonest cause of seizures in children. Most seizure disorders have a good prognosis, provided that a comprehensive approach is used for the management.